Racionální návrh léčiv s využitím farmakoforového modelování - Koščová, Pavlína; Provazník, Ivo (Chemické listy, 2016)
Development of information technologies in recent decades has facilitated also a great progress in the development of new drugs. Methods of Computer-Aided Drug Design allow us to explore the spatial interaction between the receptor and a potential drug. The review deals with a brief summary of these computational methods and is mainly focused on pharmacophore modelling, one of the modern approaches in drug design that has proved to be a useful tool.
Keywords: Pharmacophore; kvantitativní vztahy mezi strukturou a aktivitou; počítače; Quantitative Structure-Activity Relationship; farmakofor; objevování léků; racionální návrh léčiv; Computers; Drug Discovery; Software; počítačová simulace; Computer Simulation; Molecular Structure; Drug Design; software; molekulární struktura; farmakoforové modelování